Clinical outcomes of pediatric osteomyelitis - Kylie Disch; Deirdre A. Hill; Harry Snow; Walter Dehority (BMC, 2023)
Abstract Background Osteomyelitis in children may produce severe sequelae. However, the frequency and distribution of such complications by type of osteomyelitis (chronic or acute) is not well described. Methods We searched the HealthFacts® database (containing medical information on 68 million individual patients in the United States) with 238 International Classification of Diseases (ICD) version 10 codes for acute osteomyelitis and chronic osteomyelitis appearing in 2015. Outcomes were recorded for each subject, including development of limb length discrepancies, pathologic fractures, mortality, and need for multiple surgeries or prolonged orthopedic care (one to two years following diagnosis). Gender, age and season of diagnosis were also assessed. Chi-square tests were used to compare differences between categorical variables, and t-tests between continuous variables. Results Eight hundred sixty-nine subjects were included (57.4% male). Children with chronic osteomyelitis were older than those with acute osteomyelitis (median 9.5 years vs 12.0, respectively, p = .0004). Diagnoses were more common in winter (p = .0003). Four subjects died while hospitalized during the study period (two with acute osteomyelitis, two with chronic osteomyelitis). Limb length discrepancies were rare and similarly distributed between infection types (≤ 1.3% of subjects, p = .83). Subjects with chronic osteomyeltis were more likely to require long-term orthopedic follow-up (14.0% vs. 4.8% for acute osteomyelitis, p < .0001), suffer from pathologic fractures (1.5% vs < 1.0%, p = .003) and to require multiple surgeries (46.0% vs. 29.3%, p = .04). Conclusions Though infrequent, serious outcomes from osteomyelitis are more common with chronic osteomyelitis than acute osteomyelitis.